2016
DOI: 10.1097/qad.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in HIV linkage to care interventions

Abstract: Objective To synthesize qualitative evidence on linkage to care interventions for people living with HIV. Design Systematic literature review. Methods We searched nineteen databases for studies reporting qualitative evidence on linkage interventions. Data extraction and thematic analysis were used to synthesize findings. Quality was assessed using the CASP tool and certainty of evidence was evaluated using the CERQual approach. Results Twenty-five studies from eleven countries focused on adults (24 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…The study revealed that mortality was found to be higher among (65.3%). This nding is in line with the national EDHS data (2016) in which the prevalence of HIV infection among females was two times higher than males (50). Studies from African countries also support this nding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study revealed that mortality was found to be higher among (65.3%). This nding is in line with the national EDHS data (2016) in which the prevalence of HIV infection among females was two times higher than males (50). Studies from African countries also support this nding.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, two groups who were known to be either exposed or not exposed to the factor of interest in a speci c time frame were compared on the basis of outcomes of interest. The hazard risk is used as measures of estimation of the relative risk (50).…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…Concerns about loss of confidentiality associated with participating in adherence interventions emerged as a barrier in intervention implementation [15,17,45,54]. It is important to note that this barrier was reported in high income countries (HICs) [45], MIC [15], and LMIC [19,56] settings across the three well-established types of interventions, such as task shifting [15], DOT [45,54] and a mobile phone text message intervention [17]. Adolescents living with HIV and adults reported that participating in interventions could inadvertently reveal their HIV status [15,17,45,54].…”
Section: Confidentiality (Four Studies High Cerqual Confidence)mentioning
confidence: 99%
“…A systematic review of qualitative evidence of interventions for improving ART adherence can help to better understand barriers and facilitators to interventions [18,19]. It is imperative to understand potential participant harms and benefits to more effectively address health equity and human rights [20].…”
Section: Introductionmentioning
confidence: 99%
“…While large numbers of people are being initiated on ART, several research studies have found that the use of traditional health practitioners (THPs) continues to delay individuals from timeously obtaining care, and remaining in care [2427]. Furthermore, numerous studies have examined the implications of traditional medicines and practices related to HIV treatment and management [2831].…”
Section: Introductionmentioning
confidence: 99%